2015
DOI: 10.1002/2014ja020903
|View full text |Cite
|
Sign up to set email alerts
|

MESSENGER observations of multiscale Kelvin‐Helmholtz vortices at Mercury

Abstract: Observations by the MErcury Surface, Space ENvironment, GEochemistry, and Ranging (MESSENGER) spacecraft in Mercury's magnetotail demonstrate for the first time that Na + ions exert a dynamic influence on Mercury's magnetospheric system. Na + ions are shown to contribute up to~30% of the ion thermal pressure required to achieve pressure balance in the premidnight plasma sheet. High concentrations of planetary ions should lead to Na + dominance of the plasma mass density in these regions. On orbits with northwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
59
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 65 publications
1
59
0
Order By: Relevance
“…It is the strong compressional nature of this lower branch that makes this wave mode a good candidate for explaining the compressibility of the observed waves, not the upper branch as originally proposed in Boardsen et al []. As mentioned, a proton beta of ~2 would be required for the upper branch to be compressional [ Denton et al , ], such that beta is only observed in the plasma sheet tail at Mercury [ Korth et al , ; Gershman et al , ], where these waves are not observed.…”
Section: Instability Analysismentioning
confidence: 96%
See 1 more Smart Citation
“…It is the strong compressional nature of this lower branch that makes this wave mode a good candidate for explaining the compressibility of the observed waves, not the upper branch as originally proposed in Boardsen et al []. As mentioned, a proton beta of ~2 would be required for the upper branch to be compressional [ Denton et al , ], such that beta is only observed in the plasma sheet tail at Mercury [ Korth et al , ; Gershman et al , ], where these waves are not observed.…”
Section: Instability Analysismentioning
confidence: 96%
“…As proton beta ( β P ) increases, the ion‐Bernstein wave transition from the electrostatic ion‐Bernstein mode for β P ~5 × 10 −4 to a magnetic transverse dominant electromagnetic mode for β P ~0.4 (observed in the Earth's plasma sheet boundary layer) and to a magnetic compressional dominant electromagnetic mode for β P ~2 [ Denton et al , ]. Except in magnetic cavities (plasma sheet proper) at Mercury [ Korth et al , ; Korth et al , ; Gershman et al , , ], such high beta are not observed. In this paper we use warm plasma ray tracing and show that in a smaller beta plasma of ~0.1, waves that are initially transverse dominant can become compressionally dominant in a cyclic manner as they propagate in a trapped magnetic (dipole) geometry.…”
Section: Introductionmentioning
confidence: 99%
“…However, Ebert et al [] recently observed Hall magnetic field structures and Alfvénic jets at Jupiter's magnetopause near the dawn terminator, indicating that reconnection may yet play a role in mass transport. Kelvin‐Helmholtz vortices, which are observed at other planetary magnetospheres [ Hasegawa et al , ; Masters et al , ; Delamere et al , ; Sundberg et al , ; Gershman et al , ; Kavosi and Raeder , ; Ma et al , , , ], are expected to be present, but these structures at Jupiter have not yet been reported. Finally, low‐frequency MHD fluctuations with periods up to ~100 s have been observed inside of Jupiter's magnetosphere and in the magnetopause boundary layer (MPBL) [ Tsurutani et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…The solar wind interaction with Mercury also produces frequent, large flux transfer events (FTEs) observed from the subsolar region to the high‐latitude magnetopause downstream of the cusp [ Slavin et al , , , ; Imber et al , ]. Fully developed Kelvin‐Helmholtz waves are observed along the low‐latitude magnetopause, but only along the dusk flank [ Boardsen et al , ; Sundberg et al , ; Liljeblad et al , ; Gershman et al , ].…”
Section: Introductionmentioning
confidence: 99%